2015
DOI: 10.1007/s11255-015-0980-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of female gender on bladder cancer-specific death risk after radical cystectomy: a meta-analysis of 27,912 patients

Abstract: Female demonstrated worse survival outcomes than male after radical cystectomy for bladder cancer. The adoption of more intense cares for female patients was suggested after radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Anatomical differences might also explain the fact that a higher mortality in females with bladder cancer contrasts to a lower mortality in females seen in a great variety of other cancers [14]. The results of this study do not support the hypothesis that female candidates for radical cystectomy should undergo more intense treatment and follow-up [2] since the stage-adjusted mortality rates did not differ meaningfully (Table 2; Fig. 2).…”
Section: Gender and Mortality After Radical Cystectomymentioning
confidence: 56%
See 1 more Smart Citation
“…Anatomical differences might also explain the fact that a higher mortality in females with bladder cancer contrasts to a lower mortality in females seen in a great variety of other cancers [14]. The results of this study do not support the hypothesis that female candidates for radical cystectomy should undergo more intense treatment and follow-up [2] since the stage-adjusted mortality rates did not differ meaningfully (Table 2; Fig. 2).…”
Section: Gender and Mortality After Radical Cystectomymentioning
confidence: 56%
“…Female patients have been found to harbor a higher mortality risk after radical cystectomy [1][2][3]. The reasons for this phenomenon are discussed controversially [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with Siergrist et al, which found that gender was not a significant predictor of the rate of both major (Clavien grade 3-5) and minor (Clavien grade 1 or 2) complications in the perioperative period [25]. However, a recent meta-analysis of 17 studies showed female gender is associated with a higher rate of cancer specific death (CSD), which we are not able to investigate this finding due to the limitations of the NSQIP database [26]. Previously it has been suggested this gender difference is due to women presenting with more advanced disease along with sociodemographic differences and the association of gender with CSD disappears when controlling for these confounders [27].…”
Section: 4 Discussionmentioning
confidence: 92%
“…However, whether this translates into worse survival rates is still debatable. While a metaanalysis of nearly 28,000 patients showed a worse survival in women compared to men [3], several other studies showed no difference in recurrence-free or survival rates [4,5]. Moreover, survival and recurrence data on non-Caucasians patients are scarce.…”
Section: Introductionmentioning
confidence: 99%